Centralized or Decentralized: Which Governance Systems are Having a "Good" Pandemic?. Issue 2 (1st December 2020) - Gaskell, Jennifer; Stoker, Gerry
Abstract: The COVID-19 pandemic has had devastating effects across the world, yet different countries have had varying degrees of success in their attempts to manage it. One of the reasons behind the different outcomes observed so far lies in the strengths and weaknesses of different governance arrangements leveraged to tackle the crisis. In this article we examine what we can learn about the operational capacity of different democracies through their early responses to the crisis. We provide a framework of four positive qualities of multilevel governance that might lead to greater chances of positive practical outcomes and present an illustrative case study of the experiences of Switzerland and the United Kingdom (UK). We conclude with some areas for further research and investigation.